SCREENING FOR DROUGHT TOLERANCE UNDER NATURAL STRIGA GESNERIOIDES INFESTATION IN SELECTED COWPEA (VIGNA UNGUICULATA L. WALP) GENOTYPES IN KANO, NIGERIA - Hayatu, M.; Isa, A. A.; Namadina, M. M. (FUDMA Journal of Sciences, 2023)
Drought stressed and Striga gesnerioides (L.) are some of the abiotic and biotic factors affecting cowpea production in the semi-arid and sub-humid tropics. The aim of this research was to screen for drought tolerant in selected cowpea genotype infested with Striga under natural condition. Sixteen (16) cowpea genotypes were evaluated in IITA experimental farm Minjibir in Kano, Nigeria. The experiment was conducted in Randomized Complete Block Design with water stressed and well watered (as control). The parameters measured are chlorophyll, leaf canopy temperature, Striga growth and grain yield. The result showed that both chlorophyll content and Canopy temperature were reduced in the stress treatment. Varieties IT07K-292-10, IT98K-205-8, TVU-7778 and IT573-2-1 recorded the highest canopy temperature. IT98K-205-8 (70.56 SPAD value) recorded an increase in chlorophyll. The highest number of Striga emerged were recorded in IT98K-568-18 (12.00) and TVU-7778 (5.00), while IT98K-205-8, IT99K-573-1-1 and IT997-573-2-1 had no emergence of Striga. Highest Striga biomass was recorded in IT98K-568-18 (30.33g/plant), TVU-7778 (19.00g/plant) and Danila (11.33g/plant). Pod weight was found to reduce with water stress, varieties IT97K-499-35 (144.5g/plant), IT98K-1092-2 (7.0g/plant) and IT98K-506-1 (25g/plant) had the lowest pod weight, and similarly those varieties also recorded the lowest seed weight at water stress condition. The study concluded that water stress and Striga infestation reduced all the parameters measured and varieties IT98K-506-1, Danila, IT98K-1092-2 were found to be susceptible to water stress as well as Striga infestation, while varieties IT00K-1263, IT98K-131-2, IT98K-205-8, TVU-7778 were found to be tolerant to both water stress and Striga infestation.